Google web toolkit solutions : cool & useful stuff - Geary, David M. (Short cut., 2007)
The Google Web Toolkit (GWT) is a cutting-edge UI framework for Java developers, which lets you create rich, interactive user interfaces using familiar idioms from Java's Abstract Window Toolkit (AWT), Swing, and the Eclipse Foundation's SWT. If you've used any of those frameworks in the past, you're already halfway up the GWT learning curve. This short cut assumes that you have already installed GWT and have experimented with its basic features. It also assumes that you're comfortable with techniques like implementing event listeners as anonymous inner classes and know how to construct applications using panels and widgets. Some of the more advanced aspects of the GWT are explored in this short cut using two applications: an address book and a Yahoo! trip viewer. Both applications use remote procedure calls to access information on the server or an online web service. The Yahoo! Trips application also shows how you can incorporate Scriptaculous, a powerful JavaScript toolkit, to apply a useful effect for displaying results. Other cool and useful techniques, including how to implement drag and drop and how to integrate with a database using Hibernate are demonstrated. Since you'll eventually want to move your GWT application to a servlet container such as Tomcat or Resin, the process of deploying a GWT application to Tomcat with Ant is also covered. Lastly, this short cut shows how to use popup panels and deferred commands to provide a much more interactive user interface. A JAR file containing the source code for both applications can be downloaded by going to www.prenhallprofessional.com/title/0131584650.